Standardization of criteria in MacCAT‐T and MacCAT‐CR for monoclonal anti–beta‐amyloid antibodies: A Delphi study - Jonas Karneboge; Ferdinand vonBoehn; Julia Haberstroh (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract Introduction Assessing capacity to consent to treatment and participation in clinical research with monoclonal anti–beta‐amyloid antibodies is critical, especially given the frequent uncertainty in the eligible population. Capacity tends to be underestimated in Alzheimer's patients and overestimated in those with mild cognitive impairment (MCI). Methods Using the Delphi method, an international expert panel (N = 21) was surveyed in two waves. Results The participants reached consensus on 85 % of identified features, 90 % of benefits, and 88 % of risks. Discussion The resulting standard emphasizes the understanding subscale of the MacArthur competence assessment tools (MacCAT) for both treatment and research, supporting use across clinical and research settings. Despite proven utility, only 4 % of psychiatrists currently use tools like MacArthur Competence Assessment Tool for Treatment (MacCAT‐T). This consensus aims to promote wider adoption of capacity assessments, integrating them routinely into clinical practice to balance patient autonomy with beneficence.